TAṬWĪR AL-NAMUŻAJ LI TA’LĪM MAHĀRAH AL-QIRĀAH ‘ALA ASĀS MAHĀRĀT AL-TAFKĪR AL-‘ULYA WA AL-MA’RIFAH ‘AN AL-MUḤTAWA WA AL-TA’LĪM WA AL-TIKNŪLŪJIYA - Hani’atul Khoiroh; Uril Bahruddin; Umi Mahmudah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The target of high-level thinking in learning reading skills at the Abdullah Faqih Gresik Islamic Institute has not been fully fulfilled, and also has not been able to utilize modern technology, this makes learning ineffective and less enjoyable because there is no appropriate learning model. The purpose of this research is to develop a reading skill model based on Higher Order Thinking Skill (HOTS) and Technology, Pedagogy and Content Knowledge (TPACK) and determine its validity, practicality and effectiveness. This type of research is research and development with Borg and Gall steps. The results of the validation questionnaire from the test results of 88% of model component experts with good and honest averages, 80% of media experts with the same standard and 80% of learning material experts with the same average. After conducting field trials, the results showed that the new learning model was more effective than the old one. It was demonstrated by the results of the T-test value using the SPSS 22 program, which is (0.000) smaller than the T-table degree at a significance level of 0.05% (0.05). This effectiveness is also shown by the summative value results of female students with an average of 81.7 or good predicates. The theoretical results of this study indicate that the learning process based on higher order thinking skills and modern technology contributes to the thinking process of students in a comfortable and enjoyable way.